ANALISIS KEUANGAN PENDAPATAN ASLI DAERAH PADA BADAN PENGELOLA KEUANGAN DAN ASET DAERAH PEMERINTAH KOTA JAMBI - Fia, Ulfia; Wiwik Tiswiyanti, Wiwik; Intan Suri, Putri (STKIP Subang, 2026)
This study aims to analyze the financial performance of the Jambi City Government in increasing Regional Original Revenue (PAD) during the 2011–2025 period. The background of this research is based on the still low level of regional fiscal independence and high dependence on transfer funds from the central government, despite PAD showing an increasing trend from year to year. The research method used is descriptive qualitative, utilizing secondary data in the form of Regional Revenue and Expenditure Budget (APBD) realization reports obtained from the Directorate General of Fiscal Balance (DJPK) and the Jambi City Regional Finance and Asset Management Agency (BPKAD). The analysis was conducted using a regional financial ratio approach, which includes the ratios of independence, effectiveness, efficiency, decentralization, regional financial dependence, harmony, and PAD growth. The results indicate that the Jambi City Government's financial performance remains in the low to adequate category, particularly in terms of fiscal independence and decentralization ratios, which indicate a still high dependence on the central government. Meanwhile, the effectiveness and efficiency ratios show relatively good performance, although they have not been stable from year to year. Regional Original Revenue (PAD) growth tends to fluctuate, primarily due to external factors such as the Covid-19 pandemic, which has reduced regional economic activity. In conclusion, the Jambi City Government's financial performance in increasing PAD has not been optimal, necessitating a more effective strategy to explore potential regional revenue sources, improve financial management efficiency, and strengthen fiscal efficiency to support sustainable regional development.